Clinical epidemiological characterization of COVID-19 in Cumanayagua. 2021 - Narciso Águila Rodríguez; Lourdes Elena Duany Badell; Sarah Hernández Malpica; Natasha Sánchez Bouza; Yoseline César Carrero; Maidelenyis Santos Santos (Medisur)
Background: in the history of humanity, the great pandemics have represented important and terrible scourges for the human race and the development of society. Objective: to describe the clinical and epidemiological characteristics of COVID 19 in the Cumanayagua municipality, Cienfuegos province, during the year 2021. Methods: A retrospective study of a series of cases was carried out, whose universe consisted of 5,710 positive cases for COVID 19. Variables studied: cases according to months, statistical weeks, age, sex, presence or absence of symptoms, clinical manifestations, source of infection, popular council, health area and deceased. Results: The months of August and September predominated with higher positive cases and deaths, more frequent in females, as well as in young adults. The highest percentage presented clinical symptoms, cough and asthenia were the most reported symptoms, followed by headache and runny nose. Being a contact of a positive case prevailed as a source of infection, the mountainous area reported a lower frequency of cases. Conclusions: The pandemic was an event that caused anguish, restlessness and anxiety on the planet. Being aware of your history is essential to differentiate progress from your progress and thus anticipate and take action for more challenging and dire situations. To this end, knowing its clinical and epidemiological characteristics and its constant updating is valuable to conceive the behavior of the COVID-19 disease, which behaved with an increase in the period studied in the municipality of Cumanayagua.